1934. Il giuoco delle parti dietro le quinte de La Figlia di Jorio - Pieri, Marzia (Archivio d’Annunzio, 2017)
According to Silvio D’Amico and the Fascist regime, staging La Figlia di Iorio at the 1934 Volta Conference would show the world a perfect example of the rising Italian direction, especially considering that high-level international figures joined to rewrite this masterpiece in Mediterranean rustic literature, thirty years after Michetti’s and Talli’s realistic and pictorial legendary première. However, putting together avant-garde and tradition was a gamble that did not work out. Pirandello, De Chirico, Ruggeri and Marta Abba (who had been recommended) reluctantly participated in the endeavour and did not manage to meet expectations. This was the umpteenth missed opportunity in the history of Italian theatre, and d’Annunzio polemically distanced himself from it .